Islamic Law at the Grassroot; SIGMA Program at Bhasa Radio Situbondo and Its Controversy - Nawawi; Muntaha Artalim Zaim; Ahmad Azaim Ibrahimy; Yasid; Abdul Hamid Achak (Al-Ihkam, Jurnal Hukum dan Pranata Sosial, 2023)
This study explores the controversy of SIGMA (Konsultasi Agama or Religious Consultation) at Bhasa Radio 93.1 FM Situbondo as the representation of how grassroots Muslims perceive Islamic law. SIGMA is an aired interactive forum discussing current issues of Islamic law engaging a host, a speaker, and listeners. However, it sparks controversy particularly because of the stigma of a liberalist. This research, therefore, focuses on the typology of SIGMA perspective through the opinion of its speakers, genealogy beyond their thought, and the controversy that comes along. As a qualitative field study with a socio-philosophical approach, it used interviews with 14 informants consisting of SIGMA speakers and staff as well as listeners from diverse backgrounds. It turns out that; firstly, SIGMA’s perspective indicates a progressive type of thought rather than liberal as stigmatized because of the employment of maqas{id al-syari’ah during discussing the issue and making decisions afterward. Secondly, the thinking model can be traced back historically to NU (Nahdlatul Ulama’) reformists who likely use maqas{id al-syari'ah to examine Islamic law along with a progressive mindset. SIGMA speakers furthermore tend to employ advancement of ijtihad and contextual fiqh like what bahs| al-masa'il forums typically do. Thirdly, the controversy stems mainly from the negative stigma which tends to be loudly and sporadically expressed making sympathetic voices unheard. This implies how grassroots Muslims interact with Islamic law in both textual and contextual realms particularly when coping with the changing situation and dynamic methodologies.